Gender differences in the experience of loneliness in U.S. Chinese older adults. (4th March 2017) - Dong, XinQi; Chen, Ruijia
ABSTRACT: This study aimed to explore the gender differences in the experiences of loneliness in the U.S. Chinese older population. The data were drawn from the PINE study, a population-based study of U.S. Chinese adults aged 60 years and older. The Revised–University of California at Los Angeles Loneliness Scale (R-UCLA) was used to measure loneliness. Overall, older Chinese women (28.3%) had a higher rate of loneliness than older men (23.3%, p  < .001). In particular, women were more likely to sometimes or often experience a lack of companionship than men (22.9% vs. 17.3%, p  < .001). Older women living with fewer people, with lower health status, poorer quality of life, and worsening health changes over the past year were more likely than men to experience any loneliness. This study indicates that gender differences exist in the prevalence, symptoms, and correlates of loneliness. Longitudinal studies should be undertaken to understand gender differences in risk factors and outcomes of loneliness.